ALKBH2, a novel AlkB homologue, contributes to human bladder cancer progression by regulating MUC1 expression. Issue 3 (14th February 2013) - Fujii, Tomomi; Shimada, Keiji; Anai, Satoshi; Fujimoto, Kiyohide; Konishi, Noboru
Abstract : The ALKBH family of proteins are highly expressed in various types of human cancer where they are involved in tumor growth and progression. However, multiple isoforms of ALKBH exist and the effect of individual isoforms on the development of urinary bladder cancer is unknown, particularly the molecular mechanisms involved in the progression from a noninvasive to invasive phenotype. We examined the role and function of ALKBH2 in human bladder cancer development in vitro and provide the first report that suppression of ALKBH2 in a human urothelial carcinoma cell line, KU7, reduces the expression of the transmembrane mucin protein, MUC1, and induces G1 cell cycle arrest. Moreover, reduction of ALKBH2 suppressed epithelial to mesenchymal transition (EMT) via increasing E‐cadherin and decreasing vimentin expression. Transfection of MUC1 siRNA inhibited cell proliferation and EMT to the same extent as ALKBH2 gene silencing in vitro . ALKBH2 knockdown significantly suppressed MUC1 expression and tumor volume of bladder cancers in vivo as assessed in an orthotopic mouse model using ALKBH2 shRNA transfected KU7 cells. Immunohistochemical examination showed high expression levels of ALKBH2 in human urothelial carcinoma samples, especially in high‐grade, superficially and deeply invasive carcinomas (pT(1) and >pT(2)), and in carcinoma in situ but not in normal urothelium. This study demonstrates that ALKBH2 is an upstream molecule of the oncoprotein, MUC1, and regulates cell cycle and EMT, resulting in progression of urothelial carcinomas.